Nonocclusive mesenteric ischemia associated with postoperative jejunal tube feeding: Indicators for clinical management. Issue 8 (August 2020) - Albrecht, Hendrik Christian; Trawa, Mateusz; Gretschel, Stephan
Postoperative nutrition via a jejunal tube after major abdominal surgery is usually well tolerated. However, some patients develop nonocclusive mesenteric ischemia (NOMI). This morbid complication has a grave prognosis with a mortality rate of 41% to 100%. Early symptoms are nonspecific, and no treatment guideline is available. We reviewed cases of NOMI at our institution and cases described in the literature to identify factors that impact the clinical course. Among five patients, three had no necrosis and one had segmental necrosis and perforation. These patients recovered with limited resection and decompression of the bowel and abdominal compartment. In one patient with extended bowel necrosis at the time of re-laparotomy, NOMI progressed and the patient died of multiple organ failure. The extent of small bowel necrosis at the time of re-laparotomy is a relevant prognostic factor. Therefore, early diagnosis and treatment of NOMI can improve the prognosis. Clinical symptoms of abdominal distension, cramps and high reflux plus paraclinical signs of leukocytosis, hypotension and computed tomography findings of a distended small bowel with pneumatosis intestinalis and portal venous gas can help to establish the diagnosis. We herein introduce an algorithm for the diagnosis and management of NOMI associated with jejunal tube feeding.